2021
DOI: 10.1099/acmi.0.000261
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens necrotizing pancreatitis: an unusual pathogen in pancreatic necrosis infection

Abstract: Pancreatic necrosis infection (PNI) accounts for about 20–40 % of severe acute pancreatitis. PNI caused by anaerobic bacteria is unusual but when they present, Clostridium perfringens is the microorganism most commonly involved. We present a 60-year-old patient with a previous history of SARS-CoV-2, diagnosed with acute pancreatitis. During the hospitalisation he developed Clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…16S rRNA sequencing technology has been validated for the identi cation and abundance of anaerobes in samples such as blood and sputum [21,22]. Case report studies by Tang [23] and Sánchez-Gollarte [24] revealed that anaerobic infections predict a poor prognosis for IPN patients. Similarly, this study revealed that anaerobic bacteria such as Anabaena fragilis were important ora in the microbial composition of localized necrotic material in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…16S rRNA sequencing technology has been validated for the identi cation and abundance of anaerobes in samples such as blood and sputum [21,22]. Case report studies by Tang [23] and Sánchez-Gollarte [24] revealed that anaerobic infections predict a poor prognosis for IPN patients. Similarly, this study revealed that anaerobic bacteria such as Anabaena fragilis were important ora in the microbial composition of localized necrotic material in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcal species accounted for 33% of isolates, followed by Escherichia coli (22%) and Klebsiella (13%) [ 12 ]. Infections with anaerobic bacteria are rare, and clostridium perfringens are usually the primary organism involved [ 13 ]. Prevotella is a genus of gram-negative anaerobic rods that usually colonizes human mucosal surfaces, including the oral cavity, skin, and gastrointestinal tract [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of the disease has not yet been fully elucidated. C. perfringens and Klebsiella pneumoniae have been reported as causative agents of pancreatic gas gangrene [2] , [3] . Although antibiotics are not typically indicated for acute pancreatitis, we should promptly administer antibiotics since peripancreatic gas suggests a severe infection.…”
Section: Case Presentationmentioning
confidence: 99%
“…Although antibiotics are not typically indicated for acute pancreatitis, we should promptly administer antibiotics since peripancreatic gas suggests a severe infection. Moreover, treatment of pancreatic gas gangrene with antibiotics alone is insufficient [3] . Early surgical intervention is necessary in addition to antibiotics.…”
Section: Case Presentationmentioning
confidence: 99%